Hydrogen Sulfide Protects Against Ammonia-Induced Neurotoxicity Through Activation of Nrf2/ARE Signaling in Astrocytic Model of Hepatic Encephalopathy - Jin, Xiaozhi; Chen, Dazhi; Wu, Faling; Zhang, Lei; Huang, Yu; Lin, Zhuo; Wang, Xiaodong; Wang, Rui; Xu, Lanman; Chen, Yongping (Frontiers in Cellular Neuroscience, 2020)
Objective Hepatic encephalopathy (HE) characterized by neuropsychiatric abnormalities is a major complication of cirrhosis with high mortality. However, the pathogenesis of HE has not been fully elucidated. This study aimed to determine endogenous H2S in the blood of HE patients and investigate the role of H2S in a astrocytic model of HE. Methods Patients with and without HE were recruited to determine plasma H2S levels and blood microbial 16S rRNA gene. Rat astrocytes were employed as a model of HE by treatment of NH4CL. Exogenous H2S was preadded. Cell viability was measured by CCK8 assay and cell death was evaluated by LDH release. Apoptosis was determined by Hoechst 33342/PI Double Staining and Western blot analysis of apoptosis-related protein expression. Intracellular ROS levels were assessed by flow cytometer. Expressions of Nrf2 and its downstream regulated genes were examined by immunofluorescence staining and Western blot respectively. Nrf2 gene knockdown was performed by antisense shRNA of Nrf2 gene. Results There was a significant decrease in H2S levels in cirrhotic patients with HE compared to without HE. Blood microbiota analyses revealed certain strains associated with H2S production were negatively correlated with HE. In vitro, H2S markedly attenuated NH4CL-induced cytotoxicity, oxidative stress and apoptosis. This effect was mediated by Nrf2/ARE signaling and knockdown the expression of Nrf2 abolished the antagonistic effect of H2S on NH4CL-induced neurotoxicity in astrocytes. Conclusion Levels of H2S and bacteria associated with H2S production are decreased in HE, and H2S functions as the neuroprotector against NH4CL-induced HE by activating Nrf2/ARE signaling of astrocytes.